A Consumer Surplus Defense in Merger Control - Sven-Olof Fridolfsson (Research Institute of Industrial Economics (IFN), 2007)
A government wanting to promote an efficient allocation of resources as measured by the total surplus, should strategically delegate to its competition authority a welfare standard with a bias in favour of consumers. A consumer bias means that some welfare increasing mergers will be blocked. This is optimal, if the relevant alternative to the merger is another change in market structure that will even further increase the total surplus. Furthermore, a consumer bias is shown to enhance welfare even though it blocks some welfare increasing mergers when the relevant alternative is the status quo.
Keywords: L11; L13; L41; 330; Merger Control; Competition Policy; Consumer Surplus; Wettbewerbspolitik; Fusionskontrolle; Wohlfahrtsanalyse; Konsumentenrente; Wirtschaftsmodell